Diet associations in endometriosis: a critical narrative assessment with special reference to gluten - Brouns, Fred; Van Haaps, Annelotte; Keszthelyi, Daniel; Venema, Koen; Bongers, Marlies; Maas, Jacques; Mijatovic, Velja (Frontiers in Nutrition, 2023)
Endometriosis is characterized by the presence of endometrium-like tissue outside the uterus. The etiology remains largely unknown. Despite adequate treatment, patients can still experience symptoms or side effects resulting in therapy incompliance and in self-management strategies such as dietary measures is increasing. A gluten free diet is thought to be contributory in reducing endometriosisrelated pain, thereby optimizing quality of life. However, data is conflicting and currently provides no evidence for causality. This narrative review aims to put the effect of dietary self-management strategies on endometriosis in a balanced perspective, especially the effect of gluten and a gluten free diet. Several studies have found a strong overlap in symptoms, metabolic and immune responses associated with endometriosis and those associated with celiac disease, ulcerative colitis, Crohn's disease, irritable bowel syndrome and non-celiac wheat sensitivity. However, it remains unclear whether these diseases and/or disorders are causal to an increased risk of endometriosis. Some studies have found a positive effect on the risk of endometriosis, endometriosis-related symptoms and quality of life (QoL) when women either avoided certain nutrients or foods, or applied a specific nutrient supplementation. This includes the avoidance of red meat and omega-3, an increasing intake of foods rich in anti-oxidants, micronutrients and dietary fibers (e.g., fruit, vegetables) and the appliance of a gluten free diet. However, data from the available studies were generally graded of low quality and it was noted that placebo and/or nocebo effects influenced the reported positive effects. In addition, such effects were no longer seen when adjusting for confounders such as overweight, when a translation was made from in vitro to in vivo, or when the nutrients were not supplemented as isolated sources but as part of a mixed daily diet. Finally, some studies showed that long-term adherence to a gluten free diet is often associated with an impaired diet quality and nutrient intake, leading to negative health outcomes and reduced QoL. Concluding, scientific evidence on the efficacy of dietary interventions on well-defined clinical endpoints of endometriosis is lacking and recommending a gluten free diet to women solely diagnosed with endometriosis should therefore not be advised.